2012
DOI: 10.1208/s12248-012-9379-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Device Design on the In Vitro Performance and Comparability for Capsule-Based Dry Powder Inhalers

Abstract: Abstract. This study investigated the effect of modifying the design of the Cyclohaler on its aerosolization performance and comparability to the HandiHaler at multiple flow rates. The Cyclohaler and HandiHaler were designated as model test and reference unit-dose, capsule-based dry powder inhalers (DPIs), respectively. The flow field, pressure drop, and carrier particle trajectories within the Cyclohaler and HandiHaler were modeled via computational fluid dynamics (CFD). With the goal of achieving in vitro co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…For the purpose of increasing the likelihood of establishing in vitro comparability, the specific resistance of a test DPI device should be comparable to that of the reference DPI device. Furthermore, a recent study has shown that variation in the fluid dynamics of an entrained airflow within capsule-based DPIs with similar specific resistance affected powder dispersion and APSD (8). This study highlighted the importance of understanding the complex nature of flow field in the test and reference DPI devices in achieving comparable in vitro performance.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 79%
See 2 more Smart Citations
“…For the purpose of increasing the likelihood of establishing in vitro comparability, the specific resistance of a test DPI device should be comparable to that of the reference DPI device. Furthermore, a recent study has shown that variation in the fluid dynamics of an entrained airflow within capsule-based DPIs with similar specific resistance affected powder dispersion and APSD (8). This study highlighted the importance of understanding the complex nature of flow field in the test and reference DPI devices in achieving comparable in vitro performance.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 79%
“…The pressure drop of all devices was tested using a method described previously (8). The pressure drop testing system included a Dose Uniformity Sampling Apparatus (DUSA, Copley Scientific, Nottingham UK), Copley critical flow controller TPK (Copley Scientific, Nottingham UK) and a vacuum pump (GE Motors, MI, USA).…”
Section: Airflow Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…& To ensure that the targeted patients can operate the Test DPI device effectively and receive proper medication without any significant change in their inspiratory effort compared to use of the Reference DPI, it is preferable that the device resistance of a Test DPI be comparable to that of the Reference DPI. It has also been suggested that the use of a Test DPI with a comparable air flow resistance to the Reference DPI is expected to increase the likelihood of establishing SAC and APSD equivalence at different flow rates [16].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Experimental studies coupled with computational fluid dynamics (CFD) analysis were employed in this series of studies to simulate the flow field generated in the device with the purpose to better understand the effect of device design on deagglomeration. Most recently, CFD analysis was also employed to investigate the effect of carrier properties on the aerosolization (8) and in vitro comparability of two capsule-based devices (9) for the carrier-based DPIs. However, CFD analysis can only simulate the air flow pattern and is unable to take particle interactions into account.…”
Section: Introductionmentioning
confidence: 99%